Population aging in Cuba: role of the national media - Tornés Bernal, Maricarmen (2020)
The purpose of this work was to argue the problem of population aging in Cuba from the approach of the Cuban media. The central methodology used was the systematic review of publications related to the objective theme, leveraged in the use of the historical-logical and analysis-synthesis methods; that allowed to systematize the causes that condition this socio-cultural phenomenon from a multifactorial analysis, which describes the basic factors that condition the demographic problem in question. Likewise, to warn about the consequences for the country in the short, medium and long term; if the diagnosed situation continues, analyze the role of the media to mitigate this situation, explain the impact at the media level of the problem and assess the contribution of the national media in the prevention and comprehensive dissemination of the issue; Lastly, analyze the treatment of information based on journalistic objectivity and the relevance of the topic. The work concludes that population aging in Cuba is a complex and multifactorial problem that needs comprehensive, systemic and permanent alternative solutions.